Logic-based program synthesis and transformation : 26th International Symposium, LOPSTR 2016, Edinburgh, UK, September 6-8, 2016, Revised selected papers /: 26th International Symposium, LOPSTR 2016, Edinburgh, UK, September 6-8, 2016, Revised selected papers. (2017) - Unknown
No abstract available